Ultrasonography of abdominal muscles: Differential diagnosis of late-onset Pompe disease and myotonic dystrophy type 1 - Hsieh, Pei-Chen; Chang, Chun-Wei; Ro, Long-Sun; Huang, Chin-Chang; Chi, Jia-En; Kuo, Hung-Chou (Frontiers in Neurology, 2022)
Introduction: The axial muscles are more earlier and predominant involved in late-onset Pompe disease (LOPD) than myotonic muscular dystrophy type 1 (DM1). We aimed to evaluate trunk muscles in LOPD compared with DM1 using muscle ultrasonography. Methods: Patients with LOPD (n=3), DM1 (n=10), and age and gender matched healthy subjects (n=34) were enrolled for muscle ultrasonography. LOPD and DM1 patients were 20 to 59 years of age with a disease duration ranging between 7 and 30 years. A multifrequency linear transducer was used to evaluate muscle quality and muscle thickness in the trunk and extremities. Results: The quantitative muscle echo score revealed a higher Z score in trunk muscles in LOPD patients, and relatively normal on biceps, flexor digitorum groups. LOPD patients revealed significantly lower trunk muscle thickness than DM1 patients. Abdominal muscle strength was significantly correlated with trunk muscle echogenicity, trunk impairment scale, and trunk control test. The extremities sum score was correlated with the total Medical Research Council score. Discussion: The increase in quantitative muscle score in trunk muscles, relatively sparing biceps and flexor digitorum groups may be a differential diagnosis between LOPD and DM1. The ultrasound could easily visible abdominal muscles and investigate muscle echogenicity and thickness. The quantitative approach using muscle echogenicity rather than muscle thickness may show more correlation with trunk muscles’ function.